PRESUPPOSITION USED IN VOICE OVER OF TANGKIS PROGRAM ON INEWS TV MEDAN - Elia Masa Gintings, Amirul Mukmin Nasution and (LINGUISTICA, 2015)
This research focused on presupposition used in Voice Over of Tangkis program on Deli TV (now iNews TV). This research conducted by using descriptive qualitative in which the writer describes and analyze the meaning of the script of a news. The data were taken from voice over of Tangkis program on Deli TV. The findings shown that there were 305 utterances contained five from six types of presupposition. The result of this research show that voice over of Tangkis program on Deli TV tends to use Existential Presupposition (72%), Factive Presupposition (5%), Lexical Presupposition (6%), Non-Factive Presupposition (12%), and Counterfactual Presupposition (5%). The dominant type is Existential Presupposition, which means that the voice over purposed to tell the reader a news that happening to somebody especially crime such as murder and accident.